PHYSIOLOGICAL ASPECTS OF RESCUE OPERATIONS (Physical Culture and Sport: Scientific Perspective, 2024)
The aim of training is to optimize the body's functions and develop specific exercise adaptation, which is why the trainer must have knowledge in the field of physiology and biochemistry, without which he is unable to conduct training in a controlled and intentional manner. Knowledge on this subject allows him not only to quickly respond to changes in the athlete's body, but also to select appropriate training to shape a safe rescue operation. To move the body in space, a person needs energy, the only direct source of which is ATP - adenosine triphosphate, but there is very little of this compound stored in the body and therefore it needs to be constantly supplemented, especially in such a dangerous situation as saving a human life. Organizing training so as to mainly shape aerobic and anaerobic endurance requires the trainer to know the anaerobic threshold, also known as the lactate threshold, for each athlete. This is the threshold beyond which anaerobic processes play a more important role in providing energy than aerobic processes. Methods for determining this threshold should take into account individual differences in muscle fiber composition and current metabolic adaptation. By planning your training better, you can adapt your body to the extreme efforts that occur during a rescue operation.
Keywords: trainer; load; competition; control; physiological aspects